Peran World Health Organization Dalam Penghormatan Hak Asasi Manusia di Masa Pandemi Covid-19 - Andi Anugrah Pawi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
The research objective is to determine the role of non-state actors, in this case, the World Health Organization (WHO), in responding to efforts to respect human rights despite the COVID-19 pandemic. This research is motivated by the fact that many countries have committed human rights violations in this COVID-19 pandemic. Like Italy, which imposes a lockdown and does not respect other human rights, Indonesia is implementing travel tires against foreign nationals who come from the UK, where this can be said to be a form of discrimination committed against only certain citizens of the country and others. Because of this, it is essential to look from another perspective regarding respect for human rights at this time to achieve respect for human rights. As for the things that the World Health Organization has done in the form of giving a message by the Director-General of World Health Organization, saying that the COVID-19 pandemic is a global issue that must uphold human rights in its prevention and dissemination procedures, the use of the constitution of the International Health Regulations (IHR) as an effort to carry out monitoring of countries on the implementation and implementation of regulations related to the prevention of COVID-19, to providing recommendations and guidance on an ongoing basis with due regard to the humanitarian situation based on the International Covenant on Economic, Social and Cultural Rights (ICESCR, 1966), International Covenant on Political Rights (ICCPR, 1966), and the Universal Declaration of Human Rights (UDHR, 1948).